2015
DOI: 10.1136/bmjsem-2015-000005
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendinopathy—do plantaris tendon removal and Achilles tendon scraping improve tendon structure? A prospective study using ultrasound tissue characterisation

Abstract: ObjectivesThe plantaris tendon has recently been described as a possible important factor in midportion Achilles tendinopathy. Ultrasound tissue characterisation (UTC) is a method to study tendon structure (matrix integrity). The effect of plantaris tendon removal on Achilles tendon structure was studied using UTC.Design and settingProspective case series study at one centre.ParticipantsNine tendons in eight physically active and healthy patients (mean age 39 years) with chronic painful midportion Achilles ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 22 publications
2
57
0
1
Order By: Relevance
“…The tissue was obtained in the course of a previously described surgical procedure that includes plantaris tendon removal and Achilles tendon scraping [7, 45]. The isolation and culturing of primary tendon cells was carried out according to a protocol that has been routinely used in our laboratory [46].…”
Section: Methodsmentioning
confidence: 99%
“…The tissue was obtained in the course of a previously described surgical procedure that includes plantaris tendon removal and Achilles tendon scraping [7, 45]. The isolation and culturing of primary tendon cells was carried out according to a protocol that has been routinely used in our laboratory [46].…”
Section: Methodsmentioning
confidence: 99%
“…Despite extensive research, the pathogenesis is still not fully understood [4]. Nevertheless, clinical studies have shown that removing PM may result in an improvement of the Achilles tendon structure, accompanied by improved clinical VISA-A scores [18], i.e. a quantitative index of pain and function in patients with Achilles tendinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Achilles tendinopathy affects 1‐2 people per 1000 among the general population and up to 10% of elite long‐distance runners [2‐5]. Alfredson et al have recently hypothesized that the plantaris tendon (PT) may contribute to the development or perpetuation of symptomatic Achilles tendinopathy in some patients [6‐14]. The PT typically lies directly adjacent to the Achilles tendon (AT) and although smaller in size, the PT is stronger, stiffer, and less extensible than the AT (Figure 1A‐B) [6,15].…”
Section: Introductionmentioning
confidence: 99%